PROBLEMS AND PROSPECTS OF DEVELOPMENT OF BANKING CREDITING OF SMALL BUSINESS IN RUSSIA - A. Berdyshev (Вестник университета, 2018)
Practical experience of foreign countries testifies to the significant role of small business in ensuring the economic well-being of the country, which is facilitated, among other things, by a highly developed system of its financial support. In modern Russian conditions, the features of bank lending to small businesses give rise to a number of problems that complicate the opportunities for small business to use an affordable source of financing. In work on the basis of the analysis of existing problems, measures are proposed to develop a system of bank lending to small businesses.